A Wide Voltage-Ratio Dual-Output DC Converter for Charging Series-Connected Batteries - Yu Lin Juan (Energies, 2019)
In this study, a dual-output converter with a wide input voltage range is proposed for directly equalized charging of series-connected batteries without additional power conversion losses. Compared with most of the equalized charging topologies, such as the those with a multi-winding transformer or voltage multiplier, the proposed converter could be applied to different voltage conversion ratio applications. The proposed converter is capable not only of step-down but also step-up/down power conversions for different input voltage levels. By operating in discontinuous conduction mode, the diode reverse recovery losses can be eliminated and operation stability can also be enhanced. The operation principles and design criteria are both illustrated. A prototype of charging two series-connected LiFePO4 batteries is constructed. Corresponding experimental results of different input voltage levels are provided to verify the performance and validity.